Pitolisant alleviates brain network dysfunction and cognitive deficits in a mouse model of Alzheimer’s disease - Yang Zou; Linhan Yang; Jiahui Zhu; Jihua Fan; Hanrun Zheng; Xiang Liao; Zhiqi Yang; Kuan Zhang; Hongbo Jia; Arthur Konnerth; Yan-jiang Wang; Chunqing Zhang; et al. (Translational Psychiatry)
Abstract Histamine H3 receptor (H3R) antagonists regulate histamine release that modulates neuronal activity and cognitive function. Although H3R is elevated in Alzheimer’s disease (AD) patients, whether H3R antagonists can rescue AD-associated neural impairments and cognitive deficits remains unknown. Pitolisant is a clinically approved H3R antagonist/inverse agonist that treats narcolepsy. Here, we find that pitolisant reverses AD-like pathophysiology and cognitive impairments in an AD mouse model. Behavioral assays and in vivo wide-field Ca2+ imaging revealed that recognition memory, learning flexibility, and slow-wave impairment were all improved following the 15-day pitolisant treatment. Improved recognition memory was tightly correlated with slow-wave coherence, suggesting slow waves serve as a biomarker for treatment response and for AD drug screening. Furthermore, pitolisant reduced amyloid-β deposition and dystrophic neurites surrounding plaques, and enhanced neuronal lysosomal activity, inhibiting which blocked cognitive and slow-wave restoration. Our findings identify pitolisant as a potential therapeutic agent for AD treatments.